(3JjSjQ GdCYdGe HePGgH GdCFeI GdCYdGes - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJg JjSjQ GdEYdGe HePGgH GdEFeI GdCYdGe LGeYkG eG jMJGL Edjg ai GdhGbYGJ s
(3BNQgG (B:s
(3bGd GHhMfjaI heGdc jVei bjeJgG NGUI hbGd GdTGaYi jVef bjeJgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3Ydjg hbas
(3JcQGQ CjVoG JMJ Qbe (B1 (3ai GNJdGa GdabgGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3JHUQGJ GdCUd (B:s
Keywords: (3Yde GdaQGFVs